Discourse Of The Phenomenon Of Marriage Dispensation From The Legal Perspective And Sociology Perspective (Study In Jombang District) - Agus Setiyanto, Romy (Universitas Islam Malang, 2025)
Abstract: The ratification of Republic of Indonesia Law number 16 of 2019 concerning marriage and the compilation of Islamic law means the age limit for marriage has become 19 years. The reality is that in society there are many cases asking to be able to get married and have it officially registered, which has led to the existence of a marriage dispensation. Marriage dispensation is permitted by law by considering positive matters. The aim of this research is to examine the high number of applications for marriage dispensation in Jombang Regency. The method used is qualitative and empirical juridical. In empirical juridical studies, it is a type of research that analyzes and examines the operation of law in society. With this method, data collection is carried out by interviews, direct observation and also data related to the theme. Using this method will make it easier to observe phenomena in society in relation to the implementation of the Marriage Law. The data analysis used was an inductive method (Creswell, 1994). From a legal perspective, the existence of Law no. 16 of 2019 provides a marriage age limit of 19 years. Marriage dispensation will be granted by considering the impacts and benefits as well as the negative effects that occur. Meanwhile, from a sociological perspective, our society views early marriage as something normal and often forgets the consequences, marriage dispensation is a rational choice, even though the risks faced are very high. Therefore, it is necessary to increase public awareness of promiscuity and the essence of marriage